Geospatial and temporal analyses of Bean pod mottle virus epidemics in soybean at three spatial scales - Byamukama, Emmanuel Z.; Eggenberger, Sharon K.; Coelho Netto, Rosalee Albuquerque; Robertson, Alison E.; Nutter, Forrest W. (Phytopathology, 2014)
A statewide survey was carried out from 2005 through 2007 to quantify, map, and analyze the spatial dynamics and seasonal patterns of Bean pod mottle virus (BPMV) prevalence and incidence within Iowa. In all, 8 to 16 soybean fields were arbitrarily sampled from 96 counties in 2005 and all 99 counties in 2006 and 2007. Field- and county-scale BPMV prevalence and incidence data were mapped using geographic information systems software. BPMV prevalence was highest in the 2006 soybean growing season, when BPMV was detected in 38.7% of all soybean fields, 91.9% of all counties, and 100% of the agricultural climate districts. BPMV incidence at the field scale was highest in 2006, when mean statewide end-of-season incidence was 24.4%. Spatial analyses indicated that BPMV incidence was spatially clustered at the county scale in all three growing seasons. Prevalence at the county scale was clustered in 2005 and 2007 but not in 2006. Semivariogram analyses at the field scale indicated the presence of significant (P = 0.05) spatial dependence (clustering) at distances =23.4 km in 2005, 297.7 km in 2006, and 45.2 km in 2007. Data for county-scale incidence displayed a north (low incidence) to south (high incidence) BPMV gradient in each year of the survey. High county-scale BPMV prevalence and incidence levels in 2006 were significantly associated with BPMV prevalence and incidence in 2007 (P = 0.05). Soybean fields with narrow row spacings (=38 cm) were associated with higher levels of BPMV incidence. Soybean fields infected with BPMV had a higher probability of infection by Phomopsis pod and stem blight than did non-BPMV-infected fields. This study provides new quantitative tools and information to better understand the seasonal, temporal, and geographical distribution of BPMV disease risk at several spatial scales. © 2014 The American Phytopathological Society.
Keywords: Virus Rna; Genetics; Geographic Information System; Geography; Isolation And Purification; Mosaic Virus; Physiology; Plant Disease; Seed Plant; Potyvirus; Review; Risk; Season; Soybean; Statistics; United States; Virology; Comovirus; Geographic Information Systems; Geography; Iowa; Plant Diseases; Potyvirus; Risk; Rna, Viral; Seasons; Seeds; Soybeans